Assessment of Risk Factors Associated with Low-Birth-Weight Neonates - Rajesh Hadia; Rahul Trivedi; Cyril Sajan; Varunsingh Saggu; Sunil Baile; Sunil Kardani; Hemraj Singh Rajput (New Advances in Medicine and Medical Science Vol. 4, 2023)
Low birth weight (LBW) is a major public health issue worldwide and has been associated with several short- and long-term consequences. This study aimed to identify the risk factors associated with LBW neonates in a rural tertiary care hospital. The study was conducted as a prospective observational case-control study in the Department of Pediatrics (Neonatal Intensive Care Unit) and Department of Obstetrics and Gynecology. The study included a sample of 240 women who were admitted for delivery, and data was collected using questionnaires (Proforma). The results of the study showed that the area of residence, parental education, anaemia among pregnant women, mid upper arm circumference (MUAC) less than 23 cm, maternal age, and antenatal visits <4 were significant risk factors associated with LBW. The study found that 91.3% of cases were from rural areas, compared to 71% of controls from the same area. Similarly, anaemia was prevalent in both case and control groups, but it was seen as a significant predictor more in the case group. The study also recorded other factors such as parity, spacing between babies, and consumption of drugs and alcohol by pregnant women, which were found to be protective of LBW. In conclusion, this study suggests that delaying the age of first pregnancy, lacking iron/folic acid supplementation, not taking nutritional food during pregnancy, anaemia, and other factors were independently associated with LBW. These findings highlight the importance of antenatal care, proper nutrition, and education for pregnant women to prevent LBW and its associated consequences. Public health interventions targeting these risk factors can significantly reduce the incidence of LBW and its associated morbidity and mortality.